A simulation model of the Devils Hole pupfish population using monthly length‐frequency distributions. Issue 2 (28th February 2013) - Dzul, Maria Christina; Dinsmore, Stephen James; Quist, Michael Carl; Gaines, Daniel Bailey; Wilson, Kevin Patrick; Bower, Michael Roy; Dixon, Philip Michael
Abstract: The Devils Hole pupfish, Cyprinodon diabolis, is a federally‐endangered fish that is endemic to Devils Hole, a discontiguous part of Death Valley National Park in Nye County, Nevada. Due to its status, Devils Hole pupfish monitoring must be non‐obtrusive and thereby exclude techniques that require handling fish. Due to a recent decline in pupfish abundance, Devils Hole pupfish managers have expressed a need for a model that describes population dynamics. This population model would be used to identify vulnerable life history stage(s) and inform management actions. We constructed a set of individual‐based simulation models designed to explore effects of population processes and evaluate assumptions. We developed a baseline model, whose output best resembled both observed length‐frequency data and predicted intra‐annual abundance patterns. We then ran simulations with 5 % increases in egg‐larval, juvenile, and adult survival rates to better understand Devils Hole pupfish life history, thereby helping identify vulnerable life history stages that should become the target of management actions. Simulation models with temporally constant adult, juvenile, and egg‐larval survival rates were able to reproduce observed length‐frequency distributions and predicted intra‐annual population patterns. In particular, models with monthly adult and juvenile survival rates of 80 % and an egg‐larval survival rate of 4.7 % replicated patterns in observed data. Population growth was most affected by 5 % increases in egg‐larval survival, whereas adult and juvenile survival rates had similar but lesser effects on population growth. Outputs from the model were used to assess factors suspected of influencing Devils Hole pupfish population decline.